2017
DOI: 10.1016/j.jbi.2017.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Electronic health record as a research tool: Frequency of exposure to targeted clinical problems and health care providers’ clinical proficiency

Abstract: This project demonstrates the utility of the EHR as a research tool in studies of health care delivery in association with frequency of exposure of HCPs to TCPs. Subsequent steps in our research include multivariate modeling of clinical knowledge decay and randomized trials of pertinent preventive interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Data missingness is a common problem in EHR-based research. (48)(49)(50)(51)(52)(53)(54)(55)(56)) This is particularly true in a tertiary referral center such as VUMC, where patients often receive routine clinical care at other institutions. We found that adding more stringent criteria for cases did improve our PPV, but did not greatly impact the clinical characteristics of the case sets identified (Table S4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data missingness is a common problem in EHR-based research. (48)(49)(50)(51)(52)(53)(54)(55)(56)) This is particularly true in a tertiary referral center such as VUMC, where patients often receive routine clinical care at other institutions. We found that adding more stringent criteria for cases did improve our PPV, but did not greatly impact the clinical characteristics of the case sets identified (Table S4).…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, the use of EHR in biomedical research has inherent challenges due to inconsistent documentation, missing data, and inaccuracies. (48)(49)(50)(51)(52)(53)(54)(55)(56) Tertiary care EHR data often have sicker patients with denser clinical documentation and more complete data than other hospital settings. (56) COPD cases identified by our algorithm have more severe COPD based on FEV1 and FEV1/FVC measurements ( Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism for genetic discovery lies with the increasing use of electronic health records (EHRs). EHRs have become a more commonplace tool in genetics, allowing researchers to conduct studies on specific genetic conditions, including observational, epidemiological, descriptive, and comparative effectiveness studies, among others [6,7]. EHRs are also being used to recruit participants for research studies and clinical trials [8].…”
Section: Introductionmentioning
confidence: 99%